Determinants of attitude and buying intention of organic milk - Ivica Faletar; Marija Cerjak; Damir Kovačić (Mljekarstvo)
The consumption of organic milk is increasing rapidly. However, the behaviour of organic milk consumers is still not enough investigated. The purpose of this study was to determine variables which influence the attitude towards organic milk consumption, as well as variables which influence the buying intention of organic milk. Thereat, factors such as positive opinion toward organic milk and food related lifestyle, as well as level of trust in home as in EU organic food label, objective knowledge and gender of respondents showed to have a significant influence on organic milk buying intention. More precisely, a significant and positive influence on buying intention of organic milk was observed considering the belief in positive aspects of organic milk, subjective knowledge, objective knowledge, and attitude towards buying organic milk. According to the results of this study recommendations for marketing practice and especially for communication policy might be created. Communication directed to female population should use classic advertising based on functional information, while the one directed to male population should use more emotional advertising. By using classic advertising education of consumers should be performed in order to promote benefits of organic milk in regards to conventional milk.